2011
DOI: 10.3892/ijmm.2011.820
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibits the differentiation and maturation of dendritic cells and increases the production of regulatory T cells

Abstract: Abstract. The aim of this study was to characterize the effects of emodin on dendritic cells (DCs) and CD4 + CD25 + regulatory T cells (Tregs). Myeloid DCs were prepared from peripheral blood mononuclear cells of healthy human donors and treated with emodin at different concentrations. The phenotype and T cell stimulatory capacity of these DCs were analyzed. The expression ratios of CD80 and CD83 in DCs in the presence of emodin (100 µg/ml) were significantly decreased compared with that in DCs without emodin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…It remains to be determined why emodin differentially impacts CD11c + CD86 + and CD11c + CD80 + subsets of DCs in the LNs and spleens of the recipient mice. However, our results are actually consistent with a previous study showing that emodin inhibited DC maturation in vitro (53), implying that emodin indeed suppresses DC differentiation or maturation. It is also unclear how emodin reduces DC numbers.…”
Section: Figure 7 | Depleting Regulatory T Cells (Tregs) Largely Revesupporting
confidence: 93%
“…It remains to be determined why emodin differentially impacts CD11c + CD86 + and CD11c + CD80 + subsets of DCs in the LNs and spleens of the recipient mice. However, our results are actually consistent with a previous study showing that emodin inhibited DC maturation in vitro (53), implying that emodin indeed suppresses DC differentiation or maturation. It is also unclear how emodin reduces DC numbers.…”
Section: Figure 7 | Depleting Regulatory T Cells (Tregs) Largely Revesupporting
confidence: 93%
“…AE not only exerts antineoplastic and anti-inflammatory actions, but also inhibits the differentiation and maturation of dendritic cells (DCs), induces the proliferation of T lymphocytes in vitro [ 40 ], and affects Natural killer (NK) cell activity in a dose-dependent manner [ 41 ]. This suggests that AE has a significant effect on the immune system.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] Emodin also acts as an anti-inflammatory agent by inhibiting the differentiation and maturation of dendritic cells and increasing the number of regulatory T-cells. [ 23 ] Astragaloside is a main active ingredient in traditional Chinese medicine and acts both as an anti-inflammatory and antifibrotic agent,[ 24 25 ] while salvianolic acid A has been shown to have cardiovascular protective effects. [ 26 27 ] Recent studies have shown that compound Danshen dripping pills, which contain salvianolic acid A, can prevent contrast-induced nephropathy in patients with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%